Description of Motor Function and Quality of Life in Down Syndrome Children - Mailani, Rena; Bakar, Bunga Anisa Abu; Hisanah, Luthfiyah Nadza (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Down syndrome children occur due to a chromosomal abnormality in the form of an increase in one copy of the 21st chromosome to 3 chromosomes which is called trisomy 21. Down syndrome children experience physical abnormalities in the form of distinctive facial and body shapes as well as delays in motor and mental or cognitive development in the form of intellectual disability. Delays in motor development that occur in children with Down syndrome cause children's movements to be slower and daily activities tend to be done with the help of other people. Children with Down syndrome at school age are given education in special schools so that they receive an educational program that is appropriate to their development. Intellectual disability that occurs causes the educational program provided to be able to train with the aim of children being able to independently carry out their daily activities. To determine the description of motor function and quality of life in children with Down syndrome at the Depok Special Education Foundation. Methods: a descriptive study with a sample size of 89 people by measuring motor function using GMFM-88 and quality of life using TACQOL. Results: motor function of children with Down syndrome in the delayed category with moderate to poor quality of life. Conclusion: children with Down syndrome at YPLB Depok experience delays in motor function compared to their normal age, apart from that their cognitive function has less impact on their quality of life, which is moderate to poor. A training process is needed for independence and developing the talents of children with Down syndrome.